Silver powder, mixed silver powder, conductive paste, and method for producing silver powder and mixed silver powder

Silver powder with (111) plane orientation and controlled KAM value, combined with mechanical strain and mixed with fine silver powder, addresses the challenge of high resistance in electrode wiring, enhancing conductivity and printability.

JP7606563B2Active Publication Date: 2024-12-25DOWA ELECTRONICS MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023081842
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-05-17
Publication Date
2024-12-25
Estimated Expiration
2043-05-17

AI Technical Summary

Technical Problem

Existing silver powders and conductive pastes struggle to reduce the resistance of electrode wiring to 15 μm or less without disconnection during fine line printing.

Method used

Developed silver powder with a high proportion of (111) plane orientation and controlled KAM value, combined with mechanical strain and specific aspect ratio, and mixed with fine silver powder to enhance conductivity.

Benefits of technology

Achieves reduced resistance in electrode wiring during fine line printing, improving printability and conductivity of conductive pastes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606563000003
    Figure 0007606563000003
  • Figure 0007606563000004
    Figure 0007606563000004
  • Figure 0007606563000005
    Figure 0007606563000005
Patent Text Reader

Abstract

To provide: a silver powder and mixed powder, capable of achieving low resistance in electrode wiring when printed in lines; and a conductive paste using the same.SOLUTION: A silver powder comprises 20% or more but less than 95% of silver particles, the main area of a top surface of which is (111) plane or a plane close to (111) plane, and the KAM value of which is 0.4 or more but 1.0 or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silver powder, a mixed silver powder, a conductive paste, and a method for producing the silver powder and the mixed silver powder. [Background technology]

[0002] A conductive paste containing a mixture of spherical silver powder and flat flake silver powder as a filler and further containing a resin component is used in applications such as forming electrode circuits for solar cells, filling via holes, and as an adhesive for mounting components.

[0003] Patent Document 1 describes a silver paste consisting of silver powder as a filler, a resin component, and an organic solvent, in which the silver powder is a mixed silver powder consisting of a mixture of microspherical silver powder having an average primary particle size of 0.6 μm or less and extremely thin plate-like silver powder having an average primary particle thickness of 50 nm or less.

[0004] Patent Document 2 describes silver particles that are flaky and have a single crystal structure, and the maximum plane of the particles is a lattice plane (111). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-285673 A [Patent Document 2] JP 2019-173120 A Summary of the Invention [Problem to be solved by the invention]

[0006] Conventionally, the line width of electrode wiring was about 25 μm, but there is a demand to reduce the line width to 15 μm or less. In addition, when forming thin lines using conductive paste, there is a demand to be able to print without disconnection, and to further reduce the resistance of the electrode wiring.

[0007] Therefore, the present invention aims to obtain silver powder and mixed powder that can achieve even lower resistance of electrode wiring when fine lines are printed, and also to obtain a conductive paste using the same, and to provide a method for producing such silver powder. [Means for solving the problem]

[0008] As a result of intensive research by the present inventors in order to achieve the above-mentioned object, the present inventors have completed the present invention described below. That is, the gist of the present invention for achieving the above-mentioned object is as follows.

[0009] (1) A silver powder in which 20% or more but less than 95% of the total particles are silver particles in which the main region of the upper surface of the silver particle is a (111) plane or a plane close to a (111) plane, and the KAM value of the silver particles is 0.4 or more and 1.0 or less.

[0010] (2) The silver powder according to (1), in which the aspect ratio, calculated by dividing the volume-based median diameter by a laser diffraction method by the average thickness of the cross-section of the silver particles, is 1.2 or more and less than 4.0.

[0011] (3) A silver powder according to (1) or (2), in which the average thickness of the silver particles as measured in cross section is 310 nm or more.

[0012] (4) A method for producing silver powder, comprising applying mechanical energy to highly crystalline silver powder in which 30% or more of the total particles contain silver particles whose main region on the upper surface of the silver particles is a (111) plane or a plane close to a (111) plane, and in which the KAM value of the silver particles is less than 0.4, to impart distortion to the silver particles until the KAM value of the silver particles becomes 0.4 or more and 1.0 or less.

[0013] (5) A method for producing silver powder as described in (4), in which an amino acid is added to a silver chelate complex solution to prepare a solution, and then an ascorbic acid-based reducing agent is added to obtain the highly crystalline silver powder.

[0014] (6) A method for producing silver powder according to (4) or (5), in which the silver powder after the strain is imparted has an aspect ratio of 1.2 or more and less than 4.0, calculated by dividing the volume-based median diameter by a laser diffraction method by the average thickness of the cross-section of the silver particles.

[0015] (7) A method for producing silver powder described in any one of (4) to (6), in which the average thickness of the highly crystalline silver powder when measured in cross section is 310 nm or more, and the average thickness of the silver powder when measured in cross section after the strain is imparted is 310 nm or more.

[0016] (8) A method for producing a mixed silver powder, comprising mixing the silver powder according to any one of (1) to (3) with a fine silver powder having a larger specific surface area than the silver powder.

[0017] (9) A method for producing a mixed silver powder according to (8), comprising mixing the silver powders according to any one of (1) to (3) in a mixing ratio of 10 wt % to 90 wt %.

[0018] (10) A mixed silver powder containing at least silver particles in which the main region of the upper surface of the silver particle is a (111) plane or a plane close to a (111) plane, and the KAM value of the silver particles is 0.4 or more and 1.0 or less.

[0019] (11) The specific surface area after mixing is 0.20 m 2 / g or more 1.50m 2 / g or less.

[0020] (12) A conductive paste comprising the silver powder according to any one of (1) to (3), a resin component, and a solvent.

[0021] (13) A conductive paste comprising the mixed silver powder according to (10) or (11), a resin component, and a solvent. Effect of the Invention

[0022] According to the present invention, it is possible to obtain silver powder and mixed powder that can achieve low resistance of electrode wiring when fine lines are printed, and further, a conductive paste using the same. [Brief description of the drawings]

[0023] [Figure 1] FIG. 2 is a diagram for explaining a plane close to the (111) plane in the present invention. [Diagram 2] This figure shows an SEM image of a silver particle of the silver powder of Example 1, in which the main region of the upper surface of the silver particle is a (111) plane or a surface close to the (111) plane, together with an IPF map and a KAM map obtained by EBSD measurement of the upper surface of the silver particle. [Diagram 3] This figure shows an SEM image of a silver particle of the silver powder of Example 2, in which the main region of the upper surface of the silver particle is a (111) plane or a surface close to the (111) plane, together with an IPF map and a KAM map obtained by EBSD measurement of the upper surface of the silver particle. [Figure 4] This figure shows an SEM image of a silver particle of the silver powder of Example 3, in which the main region of the upper surface of the silver particle is a (111) plane or a surface close to the (111) plane, together with an IPF map and a KAM map obtained by EBSD measurement of the upper surface of the silver particle. [Diagram 5] This figure shows an SEM observation image of a silver particle in the silver powder of Comparative Example 1, in which the main region of the upper surface of the silver particle is the (111) plane, together with an IPF map and a KAM map obtained by EBSD measurement of the upper surface of the silver particle. [Figure 6] This figure shows an SEM image of a silver particle in the silver powder of Comparative Example 2, in which the main region of the upper surface of the silver particle is a (111) plane or a plane close to the (111) plane, together with an IPF map and a KAM map obtained by EBSD measurement of the upper surface of the silver particle. [Figure 7] 1 shows an SEM observation image of a silver particle relating to Comparative Example 3, an IPF map and a KAM map obtained by EBSD measurement of the top surface of the silver particle. [Figure 8] 1 is a 2000x SEM image of Example 1. [Figure 9] 1 is a 2000x SEM image of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Prior to describing the embodiments of the silver powder according to the present invention, the terms used in this specification will be explained.

[0025] <plane direction> The plane orientation of the silver powder according to the present invention is identified by mapping based on a color sample of a stereo triangular diagram with the (111) plane, the (001) plane, and the (101) plane as vertices in an orientation distribution (IPF map) measured by electron backscatter diffraction (EBSD). In this measurement, a crystalline sample on a stage in an SEM chamber is greatly tilted, and the stage tilt (Tilt) is set to 60° to 70°, and an electron beam is irradiated onto the sample at a specified incident angle, and the diffracted electrons reflected by the sample are received by an EBSD camera to obtain a Kikuchi pattern. Then, an orientation distribution (IPF map) for the upper surface of the silver particle is created. In the embodiment, an EBSD analyzer (OIM Analysis6.2 manufactured by TSL Solutions Co., Ltd.) is used to measure a measurement range of 60 μm × 180 μm with a step size of 0.30 μm. The SEM observation was performed under conditions of an acceleration voltage of 15 kV, a magnification of 1500x, and a tilt of 70°. Measurement points with low reliability, which had a reliability index (CI value) of 0.2 or less, were excluded, and an orientation distribution (Inverse Pole Figure (IPF)) map was created and evaluated. Since an electron beam irradiated to a place other than the top surface of a silver particle cannot obtain sufficient diffracted electrons or the reliability index becomes low, measurement points that are not on the top surface of a silver particle can be excluded by setting the reliability index. Therefore, the region for which the IPF map is created is defined as the top surface of a silver particle in the present invention.

[0026] <Planes close to the (111) plane> In the IPF map measured by EBSD, mapping is performed based on the color sample graph of a stereographic triangle with points indicating the (111) plane, (001) plane, and (101) plane as vertices for each point on the map. A schematic diagram of the color sample for this mapping is shown in FIG. 1. In practice, each point on the IPF map and the graph of the color sample is distinguished by RGB color. For example, the (111) plane has RGB = (0, 0, 255) (color name: blue), the (001) plane has RGB = (255, 0, 0) (color name: red), and the (101) plane has RGB = (0, 255, 0) (color name: green). And in the CSS color code of FIG. 1, the region A (region with a color close to blue) surrounded by a straight line for RGB = (0, 0, 255), RGB = (0, 85, 255), RGB = (85, 85, 255), and RGB = (85, 0, 255) is treated as the "plane close to the (111) plane" in this specification. When the main region on the upper surface of the silver particle in the IPF map during actual silver particle observation is represented by a color corresponding to region A of this color sample graph, the surface of the silver particle can be regarded as the "plane close to the (111) plane". Also, the "main region" refers to 60% or more of the region colored in this IPF map. In this specification, the ratio is obtained by evaluating 15 or more silver particles observed on the IPF map. That is, in one silver particle observed on the IPF map, if 60% or more of the upper surface of the silver particle is a plane close to the (111) plane, then the silver particle is a silver particle whose main region on the upper surface of the silver particle is the (111) plane or a plane close to the (111) plane.

[0027] <KAM value> The KAM value of a silver particle is determined by increasing the observation magnification to enlarge the field of view of a silver particle whose upper surface is mainly a (111) plane or a plane close to the (111) plane, creating a strain distribution (KAM map) measured by SEM-EBSD for the upper surface of the silver particle, and calculating the average value of the strain histogram on the upper surface of the silver particle. The KAM value of the strain distribution (Kernel Average Misorientation (KAM)) of the upper surface of the silver particle is evaluated individually for 10 or more of the above-mentioned silver particles observed on the IPF map. The KAM value according to the present invention is the average value of the KAM values ​​of the upper surface of the silver particles of 10 or more silver particles (silver particles whose upper surface is mainly a (111) plane or a plane close to the (111) plane). In the examples, the EBSD analysis conditions were a measurement range of 6 μm × 18 μm, a step size of 40 nm, and the SEM observation conditions were a magnification of 15,000 times, but the other conditions were the same as those for the IPF map observation described above. After creating an orientation distribution (Inverse Pole Figure (IPF)) map of the upper surface of the relevant silver particle, a KAM map was obtained.

[0028] <Median diameter> The volume-based median diameter of the silver powder according to the present invention is determined from the particle size distribution measured by a laser diffraction scattering type particle size distribution measuring device. In this embodiment, the case where a Microtrack particle size distribution measuring device MT-3300EXII (hereinafter simply referred to as a particle size distribution measuring device) manufactured by Microtrack Bell Co., Ltd. is used as the laser diffraction scattering type particle size distribution measuring device will be described below as an example. The particle size distribution of the silver powder may be measured by dispersing it in a predetermined dispersion medium, that is, by a wet method. In the example, 0.1 g of silver powder was added to 40 mL of isopropyl alcohol as a dispersion medium, and dispersed for 2 minutes using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., US-150T; 19.5 kHz, tip diameter 18 mm) to prepare a dispersion, and then the dispersion was subjected to a particle size distribution measuring device to measure the particle size distribution of the silver powder.

[0029] In this specification, the volume-based median diameter is also referred to as the cumulative 50% diameter or D50. The cumulative 50% diameter is the diameter at which the cumulative amount of particles on a volume basis from the small particle diameter side in the particle size distribution is 50%. Similarly, the cumulative 10% diameter is the diameter at which the cumulative amount of particles on a volume basis from the small particle diameter side in the particle size distribution is 10%. The cumulative 90% diameter is the diameter at which the cumulative amount of particles on a volume basis from the small particle diameter side in the particle size distribution is 90%. Hereinafter, the cumulative 10% diameter, cumulative 50% diameter, and cumulative 90% diameter on a volume basis may be referred to as D10, D50, and D90, respectively.

[0030] <Average thickness> The average thickness in the cross-sectional measurement of the silver particles in the silver powder according to the present invention is the average value of the thickness obtained based on the SEM observation image of the silver particle cross-section. In the examples, the SEM observation image for grasping the cross-sectional shape of the silver particles was obtained by polishing the resin-solidified silver powder with a cross-section polisher ArBlade 5000 (manufactured by Hitachi High-Technologies Corporation) to expose the cross-section, and then observing the silver particle cross-section with an SEM at a magnification of 5000 times. The thickness of the silver particles refers to the short side when each particle image in the SEM observation image of the silver particle cross-section is surrounded by a rectangle with the smallest area. The average thickness refers to the average value of the short sides measured by imaging 20 or more silver particles in the thickness measurement.

[0031] <Aspect ratio> In addition, in the silver powder of the present invention, the aspect ratio is the value obtained by dividing the volume-based median diameter by the laser diffraction method by the average thickness in cross-sectional measurement of the silver particles, and is referred to as "the aspect ratio obtained by dividing the volume-based median diameter by the laser diffraction method by the average thickness in cross-sectional measurement of the silver particles."

[0032] <Specific surface area> The specific surface area (SSA) of the silver powder according to the present invention is measured by the BET method. In the examples, the value measured by a Macsorb HM-model 1210 manufactured by Mountech Co., Ltd. is used.

[0033] The silver powder according to this embodiment will be described in detail below. In this embodiment, the silver powder refers to a powder that is an aggregate of silver particles (hereinafter, simply referred to as silver powder).

[0034] (Silver powder) The silver powder according to this embodiment contains 20% to less than 95% of all silver particles in which the main region of the upper surface of the silver particle is a (111) plane or a plane close to the (111) plane as measured by SEM-EBSD, and the KAM value of the silver particles is 0.4 to 1.0. A conductive paste using these silver particles can achieve low resistance of electrode wiring when fine lines are printed.

[0035] In the silver powder according to the present invention, the percentage of silver particles whose main region on the upper surface of the silver particles is a (111) plane or a surface close to the (111) plane in SEM-EBSD measurement is preferably 30% or more, more preferably 40% or more. Even if the silver powder is composed only of surfaces close to the (111) plane, it is more preferable that the percentage of silver particles whose main region on the upper surface of the silver particles is a (111) plane or a surface close to the (111) plane is less than 70% of the total particles. The content of "silver particles whose main region on the upper surface of the silver particles is a (111) plane or a surface close to the (111) plane" in the silver powder is the percentage of the number of silver particles whose main region on the upper surface of the silver particles is a (111) plane or a surface close to the (111) plane in IPF map (mapping based on a color sample graph) of EBSD measurement performed by dispersing and arranging the silver particles so as not to overlap as much as possible, relative to the number of all particles observed. Hereinafter, this percentage of the number is also referred to as IPF value.

[0036] Furthermore, the average KAM value obtained by evaluating 10 or more silver particles in which the main region of the upper surface of the silver particle is a (111) plane or a plane close to the (111) plane in SEM-EBSD measurement is 0.4 to 1.0, and preferably the KAM value is 0.5 or more. The silver particles of the present invention have distortion compared to silver particles that have been crystal-grown to have a (111) plane, and by having distortion with a KAM value in the range of 0.4 to 1.0, it is possible to obtain a further reduction in the resistance of the electrode wiring.

[0037] Furthermore, the silver powder according to the present invention preferably has an average thickness of 310 nm or more in cross-sectional measurement of the silver particles, and an aspect ratio obtained by dividing the volume-based median diameter by the average thickness by a laser diffraction method is preferably 1.2 or more and less than 4.0. If the aspect ratio is in the range of 1.2 or more and less than 4.0, the fine line printability is improved compared to flat silver particles having an aspect ratio of 4.0 or more. If the thickness is less than 310 nm, it is difficult to form a dense fired film, and the conductivity of the fired film is likely to decrease. In addition, the paste viscosity increases when the paste is made, and the printability of the paste may decrease. In addition, a large average thickness makes it easy to give a strain that is the above-mentioned KAM value when "mechanical energy is applied" during the production described below. The average thickness is more preferably 400 nm or more, and even more preferably 500 nm or more. In addition, it is preferably 3000 nm or less. If it exceeds 3000 nm, fine line printing may become difficult. The aspect ratio is more preferably 1.5 or more, and even more preferably 1.8 or more, and more preferably 3.8 or less, and even more preferably 3.6 or less.

[0038] It is also preferable that silver particles in which the main region of the upper surface of the silver particle in SEM-EBSD measurement is a (111) plane or a plane close to the (111) plane have a particle shape of an approximately polygonal plate or approximately polygonal column derived from the face-centered cubic crystal structure of silver. That is, it is preferable that the upper surface of the silver particle is an upper surface having a polygonal shape of an approximately polygonal plate, or an upper surface having a polygonal shape of an approximately polygonal column. Furthermore, it is also preferable that the particle shape has rounded corners, and it is sufficient that a part of the upper surface (bottom surface) or side surface of the approximately polygonal plate or approximately polygonal column is observed to be considered as a polygonal plate or polygonal column, and the corners may be rounded.

[0039] The specific surface area of ​​the silver powder according to the present invention is 0.10 m 2 / g or more 1.00m 2 The lower limit of the specific surface area is preferably 0.15 m / g or less. 2 / g or more is more preferable, and 0.20m 2The upper limit of the specific surface area is preferably 0.90 m / g or more. 2 / g or less, and more preferably 0.80m 2 It is more preferable that the molecular weight is 1 / g or less.

[0040] (Method of manufacturing mixed silver powder) It is also preferable to obtain a mixed silver powder by mixing the silver powder according to the present invention with a fine silver powder having a larger specific surface area than the silver powder according to the present invention. By mixing the silver powder according to the present invention with the fine silver powder, the filling rate of silver in the paste can be increased when the paste is made into a conductive paste, and as a result, the resistance of the electrode wiring can be further reduced. The mixing ratio of the silver powder according to the present invention in the mixed silver powder is preferably 10wt% to 90wt%. It is also preferable to mix the silver powder according to the present invention at 20wt% or more, and it is also preferable to mix at 30wt% or more. It is more preferable to mix the silver powder according to the present invention at 80wt% or less, and even more preferable to mix at 70wt% or less. The fine silver powder having a larger specific surface area than the silver powder according to the present invention can be a silver powder having an IPF value of zero, and it is preferable that the average aspect ratio of the long side / short side of the circumscribed rectangle having the smallest area is less than 1.5. Furthermore, it is more preferable that the average Heywood diameter of the fine silver powder having a larger specific surface area than the silver powder according to the present invention is smaller than the average thickness in cross-sectional measurement of the silver particles according to the present invention, and it is even more preferable that the average Heywood diameter of the fine silver powder is less than 500 nm. The average aspect ratio and the average Heywood diameter of the fine silver powder are calculated by measuring the long side / short side of the circumscribed rectangle that has the smallest area and the Heywood diameter of a total of 400 or more silver particles using an image analysis type particle size distribution measurement software (Mac-View, manufactured by Mountec Co., Ltd.) on the SEM image.

[0041] (Mixed silver powder) The mixed silver powder of the present invention contains at least silver particles in which the main region of the upper surface of the silver particle is a (111) plane or a plane close to the (111) plane, and the KAM value of the silver particles is 0.4 to 1.0. Regardless of the mixing ratio with fine silver powder having an IPF value of zero, if the mixed silver powder contains the silver powder of the present invention, the IPF map will show silver particles in which the main region of the upper surface of the silver particle of the present invention is a (111) plane or a plane close to the (111) plane. The specific surface area of ​​the mixed silver powder is 0.20 m 2 / g or more 1.50m 2 / g or less, and 0.30m 2 / g or more 1.20m 2 / g or less is more preferable, and 0.35m 2 / g or more 1.10m 2 / g or less. A more preferable range for a conductive paste that can be printed with fine lines is a specific surface area of ​​0.40 m 2 / g or more 0.80m 2 / g or less, and most preferably the specific surface area is 0.60 m 2 / g or more 0.75m 2 / g or less.

[0042] In addition, in the above mixed silver powder, the number ratio (IPF value) of the number of silver particles whose main region on the upper surface of the silver particle is a (111) plane or a plane close to the (111) plane to the total number of particles in SEM-EBSD measurement is difficult to measure because the number of particles per unit weight of the fine silver powder is large, but for example, in an IPF map containing the silver particles of the present invention within the field of view, it is preferably 0.1% or more, more preferably 1% or more. On the other hand, it is preferable that the mixed silver powder contains the silver particles in 90% or less of the total particles, more preferably 80% or less, and even more preferably 70% or less. This is because if the proportion of the silver particles is too high, there will be fewer starting points for necking due to polycrystalline particles during electrode formation by heat treatment.

[0043] (Conductive paste) The conductive paste according to the present invention contains the above-mentioned mixed silver powder, a resin component, and a solvent. The solvent, binder, etc. can be appropriately selected depending on the mode of use.

[0044] (Silver powder manufacturing method)

[0045] In explaining the method for producing silver powder according to the present invention, a silver powder containing 30% or more of all silver particles whose main region on the upper surface of the silver particles is a (111) plane or a plane close to the (111) plane and whose KAM value is less than 0.4 is called a highly crystalline silver powder. The method for producing silver powder according to the present invention is characterized in that mechanical energy is applied to highly crystalline silver powder containing 30% or more of all silver particles whose main region on the upper surface of the silver particles is a (111) plane or a plane close to the (111) plane, thereby imparting distortion until the KAM value of the silver particles is 0.4 or more and 1.0 or less. It is preferable that the highly crystalline silver powder has an average thickness of 310 nm or more in cross-sectional measurement of the silver particles. In addition, it is preferable that the average thickness of the silver particles in the silver powder obtained by applying mechanical energy is 310 nm or more in cross-sectional measurement, and the average aspect ratio is 1.2 or more and less than 4.0. In highly crystalline silver powder, in silver particles in which the main region of the upper surface of the silver particle is a (111) plane or a plane close to the (111) plane, the thickness in the direction perpendicular to the (111) plane or a plane close to the (111) plane is more preferably 310 nm or greater.

[0046] A specific embodiment of a manufacturing method suitable for manufacturing the silver powder according to the present embodiment will be described below. Note that the manufacturing method of silver powder described below is one example for realizing the manufacturing of the silver powder according to the present embodiment, and the silver powder according to the present embodiment is not limited to the silver powder manufactured by the manufacturing method described below.

[0047] First, it is preferable to prepare a silver aqueous solution as a raw material. This silver aqueous solution may be any solution containing silver ions, and may be, for example, a silver nitrate aqueous solution. The silver aqueous solution may also be a silver aqueous solution made of silver sulfate, silver cyanide, or silver acetate.

[0048] The pH of this silver aqueous solution may be adjusted, and then the temperature may be adjusted. The pH is preferably 1.0 to 5.0, and more preferably 1.5 to 3.0. For example, the pH can be adjusted using concentrated nitric acid. The silver particle size can be adjusted by adjusting the pH. The temperature of the silver aqueous solution is preferably 10°C to 35°C, and more preferably 17°C to 30°C. If the temperature is within this range, the silver particles can be recovered by reduction. Furthermore, by adjusting the temperature, the silver particle size can be optimized.

[0049] Next, it is preferable to mix a chelating compound as a complexing agent to complex the silver ions in the silver aqueous solution to form a silver chelate complex solution. As the chelating compound, for example, an EDTA-4Na aqueous solution can be used, and other examples include ethylenediamine, glycine, citric acid, malic acid, succinic acid, alkenylsuccinic acid, and DMSA. It is also preferable to add an amino acid as an additive to assist the complexation when mixing the chelating compound, and for example, an L(+)-arginine aqueous solution can be used, and other examples include L-alanine, L-asparagine, L-glutamine, L-phenylalanine, L-glutamic acid, L-glutamine, L-aspartic acid, L-glycine, and L-tryptophan. The addition of an amino acid increases the thickness of the silver particles, and a highly crystalline silver powder with an average thickness of 310 nm or more can be obtained.

[0050] Then, a reducing agent is added to the obtained silver chelate complex solution to generate and precipitate highly crystalline silver powder. At this time, it is also preferable to add a surface treatment agent at the same time to improve dispersibility when precipitating highly crystalline silver powder. As the reducing agent, a known reducing agent can be used, but it is preferable to use an L-ascorbic acid aqueous solution, an L-sodium ascorbate aqueous solution, an isoascorbic acid aqueous solution, etc., because they can be reduced even in the acidic pH range and the particle size and aspect ratio can be easily controlled. In addition, as the surface treatment agent, a fatty acid or a salt thereof can be used, for example, a stearic acid emulsion, oleic acid, hardened castor fatty acid, palmitic acid, myristic acid, lauric acid, capric acid, ricinoleic acid, linoleic acid, linolenic acid, etc. can be used.

[0051] Any method and raw materials can be used to produce the above-mentioned highly crystalline silver powder, but it is particularly preferable to add an amino acid to a silver chelate complex solution to prepare the solution, and then add an ascorbic acid-based reducing agent, because this causes the highly crystalline silver powder to grow thickly and is well dispersed, making it easy to process mechanically.

[0052] Furthermore, the highly crystalline silver powder in the slurry (suspension) obtained by such a wet reaction can be recovered as a dry powder by subjecting it to solid-liquid separation by filtration or the like, followed by washing and drying.

[0053] The slurry may be filtered using a Nutsche filter or the like, and filtration, washing with water, and drying may be performed in sequence. In the washing with water, the electrical conductivity of the washing solution is measured, and washing with water is preferably repeated until the electrical conductivity becomes 2.0 mS / m or less, and more preferably until the electrical conductivity becomes 1.0 mS / m or less.

[0054] The washed highly crystalline silver powder is preferably thoroughly dehydrated and then dried. Drying can be performed using a dryer such as a forced circulation atmospheric dryer, a vacuum dryer, or an airflow dryer. The drying temperature is preferably 100°C or less, and more preferably 80°C or less. Temperatures above 100°C are not preferred because the silver particles in the silver powder may aggregate and sinter. The drying time can be set at any time depending on the temperature, but it is preferable to set it to 5 hours or more.

[0055] Here, mechanical energy is applied to the dried highly crystalline silver powder to distort the silver particles in the silver powder until the KAM value is 0.4 to 1.0. The highly crystalline silver powder preferably has an average thickness of 310 nm or more.

[0056] In the present invention, "applying mechanical energy" refers to applying a physical force to the silver powder, for example, shear force due to the rotation of the stirring blade, collision force between silver particles, etc., mainly mechanical energy. As the device, it is preferable to use an electric mill such as a sample mill having a stirring blade rotating at high speed, or an airflow type pulverizer. In addition, in the present invention, "imparting distortion" refers to slightly distorting the crystal plane of the single crystal particle in the highly crystalline silver powder. By slightly distorting the crystal plane, it is possible to activate the crystal plane without significantly impairing the in-plane conductivity, and promote necking during the heat treatment for forming the electrode, which is advantageous for reducing the resistance of the electrode wiring. In addition, it is preferable that the sharp corners derived from the crystal plane of the generated highly crystalline silver powder are removed due to the "imparting distortion", because there is little risk of clogging during printing. Note that even if mechanical energy is applied to the silver powder as in Comparative Example 2 described later, if the aggregation is only loosened and the energy applied to the silver powder is small, the KAM value will not be 0.4 to 1.0. In order to impart a strain to the extent that the KAM value is 0.4 or more and 1.0 or less, it is necessary to apply a sufficient amount of mechanical energy.

[0057] The conductive paste using the silver particles thus obtained can achieve low resistance of electrode wiring when fine lines are printed. EXAMPLES

[0058] Examples of silver powder, conductive paste, and a method for producing silver powder will be described below.

[0059] Example 1 3000g of silver nitrate aqueous solution containing 170g of silver was prepared, and 45.4g of 67.5wt% concentrated nitric acid was added to adjust the pH, and the temperature was adjusted to 25°C. While stirring this solution, 0.43g of 4.3wt% EDTA-4Na aqueous solution (Chilest OD-50) and 10.7g of 5wt% L(+)-arginine aqueous solution were added to obtain a silver complex aqueous solution. Then, 1500g of 10wt% L-ascorbic acid aqueous solution was added to this silver complex aqueous solution, and the stirring was stopped and the solution was left to stand for 4 minutes and 30 seconds to reduce the silver complex aqueous solution. Stirring was resumed, and 2.03g of commercially available stearic acid emulsion (Cellosol 920 manufactured by Chukyo Yushi Co., Ltd., containing 82% water) was added to obtain a slurry containing silver particles.

[0060] Next, this slurry was filtered, washed with water until the electrical conductivity of the liquid after passing through the filter was 0.5 mS / m or less, and then vacuum dried at 73° C. for 10 hours to obtain highly crystalline silver powder.

[0061] As a treatment for imparting distortion, 50 g of each sample was placed into a sample mill (SK-10 model, manufactured by Kyoritsu Riko Co., Ltd.) and subjected to distortion treatment at the maximum rotation speed for 60 seconds, thereby obtaining silver powder as an aggregate of silver particles according to Example 1.

[0062] The mixed silver powder used to obtain the conductive paste has an SSA of approximately 0.6 m 2 / g~0.75m 2 The silver powder according to Example 1 and fine silver powder (AG-2-1C agent added, manufactured by DOWA Hi-Tech) were mixed in a weight ratio of 1:1 so that the silver powder had a specific surface area of ​​1.00 m / g. The IPF value of AG-2-1C agent added was zero, the volume-based median diameter (D50) was 0.80 μm, and the specific surface area was 1.00 m. 2The external shapes of more than 400 silver particles in total were measured for the SEM images of the AG-2-1C agent-added silver particles using image analysis particle size distribution measurement software (Mac-View, Mountec Co., Ltd.), and the particles were found to be spherical silver powder with an average aspect ratio of 1.3 and an average Heywood diameter of 0.34 μm.

[0063] Example 2 Silver powder according to Example 2 was obtained in the same manner as in Example 1, except that the amount of nitric acid was 30.2 g.

[0064] The mixed silver powder used to obtain the conductive paste has an SSA of approximately 0.6 m 2 / g~0.75m 2 The silver powder according to Example 2 and AG-2-1C agent added manufactured by DOWA Hi-Tech were mixed in a weight ratio of 1:1 so as to obtain a polymerizable compound having a molecular weight of 1:1 / g.

[0065] Example 3 Silver powder according to Example 2 was obtained in the same manner as in Example 1, except that the amount of nitric acid was 15.1 g.

[0066] The mixed silver powder used to obtain the conductive paste has an SSA of approximately 0.6 m 2 / g~0.75m 2 The silver powder according to Example 3 and AG-2-1C agent added manufactured by DOWA Hi-Tech were mixed in a weight ratio of 1:1 so as to obtain a polymerizable compound having a molecular weight of 1:1 / g.

[0067] Comparative Example 1 Except for not carrying out the distortion treatment, the silver powder according to Comparative Example 1 was obtained in the same manner as in Example 1. The silver powder according to Comparative Example 1 is the above-mentioned highly crystalline silver powder.

[0068] The mixed silver powder used to obtain the conductive paste has an SSA of approximately 0.6 m 2 / g~0.75m 2The silver powder of Comparative Example 1 and AG-2-1C agent added manufactured by DOWA Hi-Tech were mixed in a weight ratio of 1:1 to prepare a coating weight of 1:1.

[0069] Comparative Example 2 Silver powder according to Comparative Example 2 was obtained in the same manner as in Example 1, except that the device used for the distortion imparting treatment was changed to a coffee mill (ECG62 manufactured by Melitta).

[0070] The mixed silver powder used to obtain the conductive paste has an SSA of approximately 0.6 m 2 / g~0.75m 2 The silver powder of Comparative Example 2 and AG-2-1C agent added manufactured by DOWA Hi-Tech were mixed in a weight ratio of 6:4 so as to obtain a polymerizable compound having a molecular weight of 1.0 μm or more and a molecular weight of 1.0 μm or more.

[0071] Comparative Example 3 As the silver powder, FA-S-20 manufactured by DOWA Hitec was prepared. This silver powder was prepared by mixing roughly spherical silver powder with a lubricant and then flattening it using a vibration mill.

[0072] As for the mixed silver powder to obtain the conductive paste, since the SSA of the silver powder of Comparative Example 3 is larger than that of the other silver powders (Examples 1 to 3 and Comparative Examples 1 and 2), the silver powder of Comparative Example 3 was mixed with AG-2-1C agent added manufactured by DOWA Hi-Tech in a weight ratio of 7:3 so that the SSA when mixed would be close to the SSA after mixing of the other silver powders.

[0073] Table 1 shows an overview of the production conditions, etc. of the silver powders according to the above examples and comparative examples.

[0074] [Table 1]

[0075] (Silver powder evaluation) The silver powder was evaluated as described below.

[0076] First, the specific surface area of ​​the silver powder was measured using a Macsorb HM-model 1210 manufactured by Mountec Co., Ltd. When measuring the specific surface area, a He-N2 mixed gas (30% nitrogen) was passed through the measuring device at 60°C for 10 minutes to degas the device, and the value measured by the BET single point method was used.

[0077] The particle size distribution of the silver powder was measured using a laser diffraction particle size distribution analyzer (Microtrack Particle Size Distribution Analyzer MT-3300EXII manufactured by Microtrack Bell Co., Ltd.). Immediately before the measurement, 0.3 g of silver powder was added to 40 mL of isopropyl alcohol and dispersed for 5 minutes using an ultrasonic cleaner with an output of 45 W. The particle size distribution of the silver particles in the dispersion was then measured. The median diameter (cumulative 50% particle diameter, so-called D 50 The specific surface area and particle size distribution were also measured for the mixed silver powder in the same manner.

[0078] Next, the cross-section of the silver particles in the silver powder was observed. First, 0.7g of Specifix Resin was mixed with 0.1g of Specifix-20 Curing Agent as a hardener, and 4g of each silver powder was added and mixed lightly with a spatula. After that, the mixture was degassed for 30 minutes in a desiccator under reduced pressure, and mixed again with a spatula. The paste was placed in a mold and left at room temperature overnight to harden the resin. The resin-hardened silver powder was polished with a cross-section polisher ArBlade 5000 (Hitachi High-Tech Corporation) to expose the cross-section, and then an SEM observation image was taken with an FE-SEM IT-800SHL (JEOL Ltd.). The short side of the rectangle with the smallest area surrounding each particle image was calculated as the thickness.

[0079] Next, the silver particles were arranged on a stage with a conductive adhesive sheet laid thereon so as not to overlap, and the silver particles in the silver powder were observed by SEM and an IPF map and a KAM map were created using an EBSE-SEM. Figures 2 to 7 show SEM images of silver particles observed at 15,000x magnification, in which the main region of the upper surface of the silver particles of the silver powder according to Examples 1 to 3 and Comparative Examples 1 to 3 is a (111) plane or a surface close to the (111) plane, as well as IPF maps and KAM maps obtained by EBSD measurement of the upper surface of the silver particles. The SEM observation images are labeled with the symbol A, the IPF maps with the symbol B, and the KAM maps with the symbol C. Also, SEM observation images at 2,000x magnification showing the particle shapes of Example 1 and Comparative Example 3 are shown in Figures 8 and 9, respectively.

[0080] As described above, the plane orientation of the silver powder according to the present invention was measured using an electron backscatter diffraction (EBSD) analyzer (OIM Analysis 6.2 manufactured by TSL Solutions Co., Ltd.) with a step size of 0.30 μm in a measurement range of 60 μm × 180 μm. The SEM observation was performed under conditions of an acceleration voltage of 15 kV, a magnification of 1500 times, and a tilt of 70 °, and a map of the orientation distribution (Inverse Pole Figure (IPF)) of the upper surface of the silver particles was created by removing measurement points with low reliability having a reliability index (CI value) of 0.2 or less. Then, all the silver particles (at least 15 or more) on the IPF map were evaluated, and the proportion (%) of silver particles whose main region of the upper surface of the silver particles is a (111) plane or a plane close to the (111) plane was evaluated and used as the IPF value. In addition, the silver particles of Comparative Example 3 were observed to have a large number of small regions showing various plane orientations in the IPF map of the top surface of the silver particle (considered to be polycrystalline particles) as shown in the IPF map (symbol B) of Figure 7, even at a magnification of 1,500 times, and not a single silver particle was observed in which the main region on the top surface of the silver particle was a (111) plane or a plane close to the (111) plane, so the IPF value was determined to be zero.

[0081] Further measurements were performed by focusing on 10 or more "silver particles whose main region on the upper surface of the silver particle is a (111) plane or a plane close to the (111) plane" observed on the IPF map at a magnification of 1500 times, and increasing the magnification so that one silver particle was within the field of view. The EBSD analysis device conditions were a measurement range of 6 μm × 18 μm, a step size of 40 nm, and an SEM observation condition of 15000 times magnification, but the same measurement method was used to create an orientation distribution (Inverse Pole Figure (IPF)) map of the silver particles. Here, a strain distribution (Kernel Average Misorientation (KAM)) was obtained using only the upper surface portion of the silver particles for 10 or more of the silver particles, and the KAM value was evaluated, and the average KAM value was calculated from the KAM values ​​of the upper surfaces of 10 or more silver particles. In Comparative Example 3, an IPF map and a KAM map were obtained for polycrystalline particles by the same measurement method, and the average KAM value was calculated. The above results are shown in Table 2 below.

[0082] (Conductive paste evaluation) The characteristics of the conductive paste were evaluated as follows.

[0083] First, the conductive paste was prepared by mixing 93% by mass of the mixed silver powder obtained in the examples and comparative examples, 3.8% by mass of epoxy resin (ADEKA EP4901E), 1.0% by mass of (Mitsubishi Chemical jER1009), 0.2% by mass of curing agent (Wako Pure Chemical Boron Trifluoride Monoethylamine Complex), and 2.3% by mass of solvent (BCA: butyl carbitol acetate) at 1200 rpm for 30 seconds using a propeller-less self-rotating type mixing and degassing device (EME VMX-N360). After that, the mixture was kneaded by passing it through a three-roll (EXAKT 80S) with a roll gap of 100 μm to 20 μm to obtain a conductive paste.

[0084] A line pattern with a line width of 17 μm and a length of 150 mm was printed on the conductive paste obtained by the above procedure using a screen printer (MT-320T manufactured by Microtec Corporation) to form a film of the conductive paste. The obtained film was heated and cured at 200° C. for 30 minutes using an air circulation dryer to form a conductive film. The line resistance value of each conductive film was measured using a digital multimeter (R6551 manufactured by ADVANTEST Corporation).

[0085] The evaluation results of the silver powder, mixed silver powder, and conductive paste thereof are shown in Table 2.

[0086] [Table 2]

[0087] It was confirmed that the conductive paste using the silver powder obtained according to the present invention had a reduced line resistance compared to the comparative example.

[0088] The silver powder according to this embodiment is suitable for use as a conductive filler for conductive paste. The conductive paste using the silver powder according to this embodiment can be used to form a conductive pattern on a substrate or to form an electrode. The conductive paste using the silver powder according to this embodiment can be printed on a substrate by, for example, screen printing, offset printing, photolithography, or the like to form a conductive film such as a conductive pattern or an electrode (hereinafter, sometimes simply referred to as a conductive film). [Industrial Applicability]

[0089] According to the present invention, it is possible to obtain silver powder and mixed powder that can achieve low resistance of electrode wiring when lines are printed, and further, a conductive paste using the same.

Claims

1. A silver powder containing silver particles in which the main region of the upper surface of the silver particles is a (111) plane or a plane close to a (111) plane at 20% or more and less than 95% of the total particles, and the KAM value of the silver particles is 0.4 or more and 1.0 or less.

2. 2. The silver powder according to claim 1, wherein the aspect ratio, calculated by dividing the volume-based median diameter by a laser diffraction method by the average thickness of a cross-section of the silver particle, is 1.2 or more and less than 4.

0.

3. 3. The silver powder according to claim 1 or 2, wherein the average thickness of the cross-section of the silver particles is 310 nm or more.

4. A method for producing silver powder, comprising applying mechanical energy to highly crystalline silver powder in which 30% or more of the total particles contain silver particles whose main region on the upper surface of the silver particles is a (111) plane or a plane close to a (111) plane, and in which the KAM value of the silver particles is less than 0.4, to impart distortion to the silver particles until the KAM value of the silver particles becomes 0.4 or more and 1.0 or less.

5. The method for producing silver powder according to claim 4, wherein the highly crystalline silver powder is obtained by adding an amino acid to a silver chelate complex solution to prepare a solution, and then adding an ascorbic acid-based reducing agent.

6. The method for producing silver powder according to claim 4, wherein the silver powder after the strain is applied has an aspect ratio of 1.2 or more and less than 4.0, calculated by dividing the volume-based median diameter by a laser diffraction method by the average thickness measured in cross-section of the silver particles.

7. A method for producing silver powder as described in claim 4, wherein the highly crystalline silver powder has an average thickness of 310 nm or more when measured in cross section, and the silver powder after the strain is imparted has an average thickness of 310 nm or more when measured in cross section.

8. A method for producing a mixed silver powder, comprising mixing the silver powder according to claim 1 with fine silver powder having a larger specific surface area than the silver powder.

9. The method for producing a mixed silver powder according to claim 8, wherein the silver powder according to claim 1 is mixed so that the mixing ratio of the mixed silver powder is 10 wt % to 90 wt %.

10. A mixed silver powder containing at least silver particles in which the main region of the upper surface of the silver particle is a (111) plane or a plane close to a (111) plane, and the KAM value of the silver particles is 0.4 or more and 1.0 or less.

11. The specific surface area after mixing is 0.20 m 2 / g or more 1.50m 2 The mixed silver powder according to claim 10, wherein the silver content is 1 / g or less.

12. A conductive paste comprising the silver powder according to claim 1, a resin component, and a solvent.

13. A conductive paste comprising the mixed silver powder according to claim 10, a resin component, and a solvent.

Citation Information

Patent Citations

  • Silver paste

    JP2005285673A

  • Silver paste and electronic element

    JP2018055883A

  • Silver paste, joined body, and method for manufacturing joined body

    JP2019087396A

  • Silver powder for ink or for coating material

    JP2019173120A

  • Silver powder

    JP2022186757A